Simethicone and N-acetyl cysteine combination as premedication before esophagogastroduodenoscopy: Double-blind randomized controlled trial - Krishnamurthy, Veeraraghavan; Joseph, Abel; Venkataraman, Shreyas; Kurian, George (Endoscopy International Open, 2022)
Background and study aims Esophagogastroduodenoscopy (EGD), the most common method used for diagnosing upper gastrointestinal diseases, is often limited by the presence of foam and mucous. Thus, this study was designed to detect whether the combination of simethicone with N-acetyl cysteine (NAC) as premedication before EGD improves mucosal visualization.Patients and methods A total of 768 consenting patients were enrolled in this prospective, double-blind, randomized placebo-controlled trial in four groups (A: simethicone + N-acetyl cysteine; B: simethicone alone; C: NAC alone; and D: placebo). After 20 minutes of consuming the corresponding solution, EGD was done and multiple images were obtained from the esophagus, stomach, and duodenum. Based on the various images obtained, the study parameters were calculated. Statistical Analysis Software (SAS) was used to analyze the results using Kruskal-Wallis with the Bonferroni correction method.Results The study population consisted of 57 % men and the mean age was 44.18 years. Each group was randomized with 192 participants. Group A (combination of simethicone + NAC) premedication had the lowest total mucosal visibility score of 8.31, a significantly lower score for mucous/bubbles obscuring the vision, and less time to complete the procedure. Also, 81 % of the participants in group A did not require flushing to clear the mucous/bubbles. There were no side effects due to this premedication in any of the groups.Conclusions  Using simethicone and NAC combined for premedication may improve the quality of EGD.